1917 Or. Gen. and Special Laws 808, ch. 377, § 11 - (:unkn) unknown (My University, 1917)
Provided that noncitizens convicted of carrying a deadly weapon are guilty of a felony and subject to up to 5 years ' imprisonment.
Keywords: POSSESSION - DANGEROUS PERSONS